Bucculatricidae associated with Asteraceae in China, with one new species (Lepidoptera: Gracillarioidea) - Wang, Encui; Li, Wei; Liu, Tengteng (Zootaxa, 2020)
Asteraceae comprises one of the major host plant families for Bucculatricidae and Artemisia is the most exploited host genus, however, not a single record of Bucculatrix species feeding on Asteraceae is confirmed in China. One new species, B. duanwuia Liu, sp. nov., feeding on Artemisia princeps Pamp. (Asteraceae), is described from China, supplemented with illustrations of leaf mines and pupa, biology and DNA barcodes. Bucculatrix notella Seksjaeva, 1996 is recorded for the first time in China and DNA barcodes are provided aiding species separation for the first time.